Walter Eucken und der Staat: Zum Zusammenhang von wirtschaftlichem und politischem Liberalismus 1918 - 1934 - Uwe Dathe (OrdnungsPolitisches Portal (OPO), 2009)
Today we have a paradoxical situation in Germany's public debates on the order of society and economy. The absolute majority of all voters blame the state for a neoliberal economic and social policy, but the state gives up more and more ordnungspolitische ideas. If we look for causes for the refusal of the Freiburg School ordoliberal programme we can observe a very negative attitude towards the idea of a free and fair competition. Instead of hard efforts in order to promote the idea of competition both the majority of politicians, journalists, intellectuals and the majority of German voters plead for a stronger influence of the state in all spheres of the society. This situation is similar to this one in Germany after the First World War, when also both the majority of population and the majority of the intellectual and political elites tended to prefer antiliberal or nonliberal concepts in politics and economy. Two of the major prophets of German ordoliberalism, who had developed a positive programme for a free and socially aware market competition as well as for a liberal democracy, Walter Eucken and Alexander Rüstow, shared for a relative long time (Eucken until to the end of the 1920s) antiliberal economic and political positions. On the basis of unpublished letters and documents I want to describe first the rightwing antiliberal context of Eucken and the leftwing one of Rüstow and second their way to ordoliberal positions. To show both Eucken's and Rüstow's gradual development from antiliberal to ordoliberal ideas I will my description focus on their attitude towards the idea of economic and politic competition. The view on the example of Eucken and Rüstow could give any reasons to hope that the prevailing antiliberal attitudes towards necessary political and economic reforms are not the last word in public debates.
Keywords: 330; Ordo-liberalism; Freiburg School of Economics; Walter Eucken; Alexander Rüstow